Estrategia organizacional : una propuesta de estudio (2014)
The strategy concept in the context of business organizations is one of the topics of great interest in the affairs of management. However, the proposal of new approaches have not significantly contributed to progress in the study of strategy. Stagnation is evident, and for this reason this paper outlines a proposal that brings together some of the challenges for the study of strategy. The paper presents an overview, and sets out possible ways forward to contribute to the organization’s sustainability